2022
DOI: 10.1128/spectrum.01702-22
|View full text |Cite
|
Sign up to set email alerts
|

Conjugative Transfer of Acute Hepatopancreatic Necrosis Disease-Causing pVA1-Type Plasmid Is Mediated by a Novel Self-Encoded Type IV Secretion System

Abstract: The pathogenic pVA1-type plasmids that carry pirAB toxin genes are the genetic basis for Vibrio to cause acute hepatopancreatic necrosis disease (AHPND), a lethal shrimp disease posing an urgent threat to shrimp aquaculture. Emerging evidence also demonstrate the rapid spread of pVA1-type plasmids across Vibrio species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…It can, however, not be excluded that substrate recognition is mediated by TraG which is encoded next to the virB T4S gene cluster on plasmid pXCV38 and shares 23% amino acid identity with VirD4 ( Figure 1 and Figure S2 ). Since TraG-like proteins were shown to contribute to T4S ( Schröder et al., 2002 ; Khara et al., 2021 ; Wang et al., 2022 ), we analyzed a possible interaction of TraG with components and putative T4S substrates of the VirB-like T4S system. When analyzed by BACTH assays, TraG interacted with itself, with the predicted ATPase VirB11 and the structural component VirB10 but not with the potential T4S substrate TraI ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It can, however, not be excluded that substrate recognition is mediated by TraG which is encoded next to the virB T4S gene cluster on plasmid pXCV38 and shares 23% amino acid identity with VirD4 ( Figure 1 and Figure S2 ). Since TraG-like proteins were shown to contribute to T4S ( Schröder et al., 2002 ; Khara et al., 2021 ; Wang et al., 2022 ), we analyzed a possible interaction of TraG with components and putative T4S substrates of the VirB-like T4S system. When analyzed by BACTH assays, TraG interacted with itself, with the predicted ATPase VirB11 and the structural component VirB10 but not with the potential T4S substrate TraI ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, a draft genome sequence showed that a V. harveyi isolate could cause AHPND in shrimp in northern Vietnam ( 16 ) . Studies showed that plasmid-mediated interspecies transfer of the hazard genes could have occurred in different Vibrio species, including V. parahaemolyticus , V. campbellii , and V. owensii ( 17 , 18 ) and that conjugative transfer of the AHPND-causing pVA1-type plasmid carrying the hazard genes is mediated by a novel self-encoded type IV secretion system ( 19 ). Such methodologies provide direct guidelines for uncovering the virulence factors and pathogenic mechanism of Vp TPD .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1 , 5 different Vibrio species have so far been confirmed to contain pirA/pirB genes in their plasmids. Several studies have revealed that different Vibrio species may transfer pVA1-like plasmid from an AHPND-causative strain to a non-AHPND-causative strain through horizontal transfer [ 31 34 ] . It should also be noted that transposase genes are usually found around the Vibrio pirA/pirB genes [ 3 , 9 , 22 , 35 36 ] .…”
Section: Ahpnd-causing Pira Vp /Pirb ...mentioning
confidence: 99%